MORPHOFUNCTIONAL ASSESSMENT OF THE FEATURES OF MANIFESTATIONS OF ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES - Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. To date, the issues of structural restructuring of the respiratory part of the lungs in connection with the restructuring of the microcirculatory bed in patients with acute purulent-destructive lung diseases remain insufficiently studied. Material and methods. The study is based on data from 175 patients, including 129 patients with acute lung abscesses, 22 patients with pulmonary gangrene and 24 patients with chronic bronchitis. Morphometric studies were carried out using ImageJ graphics packages. Results. In patients with acute abscesses and gangrene of the lungs, certain associated changes in the large bronchi of the catarrhal and sclerotic bronchitis, with a predominance of dystrophic changes, denudation of basal cells, enlargement of intercellular spaces and instability of the bronchial epithelium, which is manifested by the proliferation of goblet cells and a nested change in the functional activity of the cells of the epithelial layer. Conclusion. Morphological and immunohistochemical studies revealed stereotyped variants of the structural reorganization of the microcirculatory bed of the respiratory part of the lungs.